Genome-wide identification and expression pattern of SnRK gene family under several hormone treatments and its role in floral scent emission in Hedychium coronarium - Wang, Chutian; Abbas, Farhat; Zhou, Yiwei; Ke, Yanguo; Li, Xinyue; Yue, Yuechong; Yu, Yunyi; Yu, Rangcai; Fan, Yanping (PeerJ, 2021)
The SnRK (Snf1-Related protein Kinase) gene family plays crucial roles in various plant signaling pathways and stress-adaptive responses including biotic and abiotic stresses via activating protein phosphorylation pathways. However, there is no information available on the role of the SnRK gene family in Hedychium coronarium. H. coronarium is an important crop widely cultivated as an ornamental plant, herb, spice, or condiment. In this study, 60 HcSnRK genes were identified from the H. coronarium genomic and transcriptome data. Phylogenetic and gene structure analysis showed that the HcSnRK genes were divided into three groups (HcSnRK1, HcSnRK2 and HcSnRK3) and among them HcSnRK3 subfamily was further subdivided into two clades according to the number of introns. Chromosome localization analysis showed that HcSnRK genes were unevenly mapped onto all chromosomes, and the Ka/Ks ratio of 24 paralogues includes four tandems and 20 segmental duplications indicated that the HcSnRK gene family underwent a purifying selection. Cis-regulatory elements analysis suggested that the HcSnRK genes respond to multiple hormones and other stresses. The responsiveness of HcSnRK genes to several hormones was analyzed by quantitative real-time PCR. Based on the different transcriptome data, two candidates HcSnRK genes (HcSnRK2.2 and HcSnRK2.9) were screened out for further characterization . The subcellular localization experiment revealed that both genes were located in the nucleus and cytoplasm. Moreover, virus-induced gene silencing (VIGS) of HcSnRK2.2 and HcSnRK2.9 significantly reduced the floral volatile contents by suppressing the expression of terpene synthase genes (HcTPS1, HcTPS3, and HcTPS5), indicating that HcSnRK2.2 and HcSnRK2.9 genes play an important role in the regulatory mechanism of floral aroma. These results will provide novel insights into the functional dissection of H. coronarium SnRK gene family.
Keywords: SnRK; Hedychium coronarium; Hormones; Stress responses; Floral scent